Microbial composition and non-surgical periodontal treatment of aggressive periodontitis: Two case reports - DOĞAN, BAŞAK (My University, 2019)
The objective of this case report was to characterize the subgingival microbiological profiles of two patients with generalized aggressive periodontitis (GAgP) and to evaluatethe clinical outcomes of non-surgical periodontal treatment(NSPT) over a 6-months period. Pooled subgingival samplesof two patients who referred to our clinic and diagnosed withGAgP were collected and analyzed for the presence of 300species/phlotypes using Human Oral Microbe IdentificationMicroarray analysis. NSPT was performed within 3-week period. Clinical parameters were measured at baseline, 3 and6 months after NSPT. Recall visits were performed every 2weeks during the first 3 months and every 4 weeks up to 6months. All samples harboured a total of 61 species and 32species were common in both patients. First patient had 17and the other had 12 distinct species. High levels of Filifactor alocis, Porpyromonas gingivalis, Campylobacter concisusand rectus, Fusobacterium nucleatum and Desulfobulbusspp. were detected in both patients while Aggregatibacter actinomycetemcomitans was found in none of them. Six monthsafter NSPT, all clinical parameters were improved in two A. actinomycetemcomitans-negative GAgP patients. In addition towell-recognized periodontal pathogens the presence of highlevels of Filifactor alocis and Desulfobulbus spp. seem to beassociated with GAgP.

Bu olgu raporunun amacı iki generalize agresif periodontitis (GAgP) hastasının subgingival mikrobiyolojik profilini belirlemek ve cerrahi olmayan periodontal tedavinin (COPT) 6 aylık klinik sonuçlarını sunmaktır. Kliniğimize başvuran iki GAgP hastasının havuzlama yöntemiyle toplanan subgingival örnekleri, 300 tür/filotipin varlığını belirlemek için Human Oral Microbiome Identificaition Microarray analizi kullanılarak incelendi. COPT 3 hafta içinde uygulandı. Klinik parametreler tedavi öncesi, sonrası 3. ve 6. aylarda kaydedildi. Hastalar, ilk 3 ayda 2 haftada bir, son 3 ayda 4 haftada bir kontrol seanslarına çağırıldı. Tüm örneklerde toplam 61 türe ve iki hastada ortak 32 türe rastlandı. İlk hastada 17, diğer hastada 12 farklı tür tespit edildi. İki hastada da yüksek seviyede Filifactor alocis, Porpyromonas gingivalis, Campylobacter concisus and rectus, Fusobacterium nucleatum and Desulfobulbus spp. saptanırken Aggregatibacter actinomycetemcomitans tespit edilmedi. COPT sonrası altıncı ayda A. actinomycetemcomitans-negatif iki GAgP hastasının tüm klinik parametrelerinde iyileşme olduğu gözlendi. Bilinen periodontal patojenlere ek olarak yüksek seviyedeki Filifactor alocis ve Desulfobulbus spp.’nin varlığının GAgP ile ilişkilendirilebileceği düşünülmüştür.
Agresif periodontitisin mikrobiyal i̇çeriği ve cerrahi olmayan periodontal tedavisi: İki olgu sunumu
Keywords: Diş Hekimliği